ANALISIS DAMPAK FASILITAS PEMBIAYAAN DENGAN PRODUK â€œQARDHUL HASAN UMKMâ€ TERHADAP PENINGKATAN PENDAPATAN USAHA UMKM BINAAN EL-ZAWA UIN MALIKI MALANG - Hamdi, Muhammad Nurul; Handayani, Latifah Safitri; Nurjanah, Evi (IQTISHODUNA, 2017)
Abstract: Nowadays, stretching the entrepreneurial communitiy is quite dominate in Indonesia. Evident fromhis contributions in the history of the national economy are quite significant in 1998, Small Medium Enterprisescan be seen as the saviour of the valve in the process of national economic recovery, both in pushing the paceof economic growth as well as the absorption of labour. Based on the data of the Ministry of cooperatives andSMEs in 2012, Small Medium Enterprises sector is the sector with the largest economy with a national economicprosentasi the involvement of the offender of 99.99%. The sector absorbs the 97.15% of the labour force inIndonesia, and contributing to GDP on the basis of the applicable rates of 6.23%.The purpose of this study isto examine, test, and evaluate the impact of financing facility with the productsâ€™ qardhul hasan small mediumenterprisesâ€™ increased revenues against the small medium enterprises assisted el-Zawa Uin Maliki Malang.The population of this research are all Small Medium Enterprises that constitute the built el-Zawa at onceusing a financing facility with dana Qardh al-Hasan is 84. 30 of Small Medium Enterprises such as researchsamples.The results show that Qardhul Hasan SMEC products can increase the income of clients. In addition,the performance of the services provided by the customer is reasonably satisfied by the clients.